Choice of laws in international commercial arbitration - Günaydın, Onur (My University, 2007)
Milletlerarası ticari tahkim günümüz ticari hayatında oldukça yoğun bir öneme sahiptir. Bu konu genel itibariyle taraflar arası seçilmis olan kurallara göre ya da hakem heyetine göre çözümlenmektedir. Ancak günümüzün karmasık ve iç içe geçmis olan düzenlemelerinin bulunduğu bu ortamda konu bir takım uluslararası anlasmalarla çözülmektedir. Basit bir uluslararası ticari tahkimde dahi dört ayrı noktada uygulanacak hukuk düzenlenebilmektedir. Bunlardan biri, tanıma ve tenfize uygulanacak hukuk. Bir diğeri, tahkim yargılama hukukuna uygulanacak hukuk. En önemlisi olan, tahkim heyetince uyusmazlığın esasına uygulanacak hukuk ve son olarak da tahkim kararının tanınması ve tenfizinde uygulanacak hukuktur. Kimi zaman, uygulanacak bu dört hukuk sisteminin aynı olması veya farklı hukuk sistemleriyle çözülmesi mümkündür. Örneğin, Đsviçre’de bulunan bir tahkim yargılamasında tahkim yeri hukuku Đsviçre hukuku olsa da, sözlesmenin hukuku olan Đngiliz hukuku uyusmazlığa uygulanabilecektir. Uygulamada, tarafların hukuk seçiminde bulunmamaları, farklı hakemlerin farklı yaklasımları olabileceği göz önüne alınacak olursa, uyusmazlığın bir belirsizlik altında kalmasına neden olacaktır. Bu durumda iliskiye en yakın bağlantılı hukuk uygulanması yöntemi devreye girecektir. Bu halde, uygulanacak hukuk konusunda evrensel bir kural olmadığından, bazı hukuk sistemlerine göre hakemler “kanunlar ihtilafı kuralları” çerçevesinde karar vereceklerdir. Ancak bugün, tahkim heyetinin kendi hukukunu belirlemesi yerine, çağdas bir takım konvansiyonlar veya tahkim kuralları devreye girmistir. Taraflar, bu sorunun çözümünde hakem kurulunun etkili olmasını arzu etmiyorlarsa çözüm kendilerinin elindedir. Aksi halde bir uyusmazlık meydana geldiğinde, daha tahkim yargılamasının en basında taraflar zaman ve para harcamak durumunda kalacaklardır. Bu nedenlerle, ticari tahkim anlasmalarına islevsel bir kural koyularak sözlesmenin gerekleri yerine getirilirken uygulanacak ve uyusmazlık çıkması halinde uyusmazlığa uygulanacak hukuk belirlenmesinde büyük fayda vardır.

Today, international commercial arbitrations take place extensively in different parts of the world. In general, it is proceeded in accordance with rules agreed by the parties or laid down by the arbitral tribunal, other than any reference to any outside system of law. The present system of international commercial arbitration is effective because of being in a circumstance of complex system of laws. These laws include international treaties, beside the national laws of many different countries. Even a simple international commercial arbitration may require reference to four different systems laws. Firstly, law governing recognition and enforcement. Then there is the law which governs the procedures of arbitration. Then as the most significant issue, there is the law or the set of rules which arbitral tribunal has to apply to the merits of that dispute. Finally, there is the law which governs recognition and enforcement of the award of the arbitral tribunal. We sometimes see that these laws may be the same. The law governing arbitral proceedings can also be the law applicable to the merits of the dispute or not. The applicable law may be a different system of law. For example, an arbitral tribunal sitting in Switzerland, governed by Swiss law as the law of the place of arbitration, may well be required to apply English law as the proper law of the contract. Practically, the determination of an applicable law in the absence of the parties' choice can cover the dispute with an uncertainty, when it is considered that different arbitrators having different approaches. While the method of applying the law most closely connected to the transaction seems to be the emerging common practice in this regard, parties are better advised to put this matter beyond doubt by stipulating their own choice of law. For the foregoing reasons, in case of an absence of an applicable law, there cannot be a universal rule. According to some systems of law, an arbitral tribunal should follow the rules of conflict of the seat of arbitration. Presently, there are contemporary conventions and rules of arbitration for giving a strong tendency to arbitral tribunals in making their choice of law, instead. If the parties do not wish the arbitral tribunal to be effective, the solution is in their hands. Otherwise the parties may spend time and money while this preliminary point is being resolved, in the case a dispute arises. Consequently, every national contract should include a functional clause that selects the governing substantive law with the purposes to govern both for the performance of the contract, and the merits of the substance in case a dispute arise.
Keywords: Avrupa Birliği Hukuku; Ticari Tahkim, Uluslararası